2015
DOI: 10.5546/aap.2015.133
|View full text |Cite
|
Sign up to set email alerts
|

Alta frecuencia de variación de la secuencia de la mutación E148Q en niños con fiebre mediterránea familiar en el sureste de Turquía

Abstract: Alta frecuencia de variación de la secuencia de la mutación E148Q en niños con fiebre mediterránea familiar en el sureste de Turquía High frequency of E148Q sequence variation in children with familial Mediterranean fever in southeast Turkey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…FMF, an autoinflammatory disease, is very common in Turkey. [ 22 ] Although it is accepted as an autosomal recessive disease, there are a great number of patients who do not have any MEFV gene mutations. [ 19 ] Thus, findings have been reported which implicate that pathological factors in genetic-negative patients may be effective in the appearance of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMF, an autoinflammatory disease, is very common in Turkey. [ 22 ] Although it is accepted as an autosomal recessive disease, there are a great number of patients who do not have any MEFV gene mutations. [ 19 ] Thus, findings have been reported which implicate that pathological factors in genetic-negative patients may be effective in the appearance of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] The most frequently reported mutations in Turkey were M694V, V726A, M680I, E148Q, R761H, and P369S. [ 22 ] The frequency of these mutations in FMF patients is much higher when compared with other mutations. These studies showed that the 12 MEFV gene mutations scanned can make up a great majority (at least 95%) of MEFV gene mutations that may be seen in a population.…”
Section: Introductionmentioning
confidence: 99%